Electron- and proton-impact excitation of He-like uranium. (July 2015) - Gumberidze, A; Thorn, D B; Fontes, C J; Najjari, B; Zhang, H L; Surzhykov, A; Voitkiv, A; Fritzsche, S; Banaś, D; Beyer, H; Chen, W; Currell, F; et al.
Synopsis: In this contribution, we present an experimental and theoretical study of the proton- and electron- impact excitation effects in helium-like uranium ions in relativistic collisions with different gaseous targets. The experiment was carried out at the experimental storage ring at GSI Darmstadt. Our experimental results are in agreement with predictions of the state-of-the art theory which treats both processes within the relativistic framework.